Impact of Biofertilizer Application and Soybean Cultivar Selection on Intercropping: A Study of Growth and Yield Performance - Rahma Harti, Adi Oksifa; Sakhidin; Muhammad Rif'an; Totok Agung; Ida Marina (International Journal of Advanced Multidisciplinary, 2023)
This study examines how the use of biofertilizer and intercropping methods impacts the growth and pod yield of different soybean cultivars. The research involved six high-quality soybean cultivars, which were treated with Fermented Liquid Organic Fertilizer (LOF) Azolla at various doses. The researchers also considered environmental factors and soil fertility conditions during the evaluation. The findings revealed that environmental factors play a crucial role in influencing the growth of soybean plants. Additionally, suboptimal soil fertility, as well as pest, disease, and weed infestations, presented challenges to soybean productivity. Through careful analysis, the researchers identified that cultivar K2 (Anjasmoro) treated with a dose of 250 ml/L LOF displayed the best performance. Notably, positive correlations were observed between plant height, number of filled pods, and seed weight per plot. The use of biofertilizer and intercropping systems demonstrated significant potential in promoting sustainable soybean productivity. Consequently, this study contributes to the development of sustainable farming practices and offers insights to enhance soybean production in an eco-friendly manner.